Comparing the effects of two methods of group education and peer education on sexual dysfunction of menopausal women: A randomized controlled trial - Zahra Vakili; Mahnaz Noroozi; Soheila Ehsanpoor (Wolters Kluwer Medknow Publications, 2019)
Background: Sexual problems could cause severe personal discomfort and affect interpersonal relationships. Considering that selection of appropriate methods has an important role in success of the education, this study was conducted to compare the effects of two methods of group education and peer education on sexual dysfunction of menopausal women. Materials and Methods: In this randomized controlled trial, 108 menopausal women were allocated into three groups in the health centers of Isfahan, Iran. After educating four menopausal women, educational sessions were conducted by them for the participants (36 women) in the peer groups. Two educational sessions were conducted by the researcher in the group education. The control group received no intervention. Before and 1 month after the intervention, female sexual function index was completed by the participants. Data were analyzed using descriptive and inferential statistics (one-way analysis of variance, paired t-test, Chi-square, Kruskal-Wallis, and Post hoc LSD test). Results: The total mean score of sexual function and its domains in the peer education and group education groups was significantly higher than the control group after the intervention (F2, 93= 23.52, p < 0.001); but the difference between the peer education group and the group education group was not statistically significant. Conclusions: Both methods of peer education and group education have been effective in improving the sexual function of menopausal women. So, considering the advantages of peer education such as its low cost, affordability, and no need to train specialized individuals, its implication in educational programs for menopausal women is recommended.